Precarização do trabalho dos assistentes sociais dos Centrosde Referência da Assistência Social de Campina Grande - Dantas, Kallyne Lígia Dantas (2010)
The present work is the result of a field research carried out social assistants who work in Centro de Referência de Assistência Social (CRAS) in the municipality of Campina Grande – PB. Studied the precarious of labor conditions of these professionals, with the objective to analyze as changes, which occurred in the relations of work, while a worldwide phenomenon had in bonds of work of public institutions and what implications thereof in the activity of the professional Social Service. The study assumed the hypothesis that the professionals of CRAS in Campina Grande have precarious and that this process of impoverishment of the contractual conditions focuses negatively on the practice of social workers, since the forms of integration and the limits set by its objective conditions impose obstacles to professional practice. The theoretical-methodological referential adopted is based on historic design critical thinking-dialectic, that part of the data provided by practical reality and examines the whole of their historical determinations, observing the relationship between the particular and the universal. The approach used is the quantitative-qualitative and instruments for data collection were the documentary analysis, observation and semi-structured interview. The assessment of such data guided-if the technique of content analysis, in addition to theoretical analysis in the light of theoretical-analytical more universal, which enabled contextualize the particularity of the profession in national and local area, recovers the historical movement and the change in direction policy of the profession. Thus, the Social Service was discussed in the context of neoliberalism and productive restructuring, which characterizes the precarious work. The research revealed that the ingress of professionals in CRAS is realized in a condition of contract precarious by means of an evaluation of curriculum riddled with too many by trafficking of influences, constitutional violating the prerogative of recruitment through the public tender. Ultimately, we infer that all social assistants are inserted, in CRASs in Campina Grande, has been precarious condition that requires a position of submission of the professional in the space socio-occupational, which undermines the quality of services and the materialization of Ethical-Political Project of the profession.